Improving pedestrian facilities in Kuantan central business district (CBD) area : pedestrian lighting - Nor Amira Aini, Ismau (2019)
This research is conducted to improve the pedestrian infrastructure in Kuantan central-business district (CBD) area specifically on pedestrian lighting. Pedestrian lighting is defined as any lighting which illuminates the pedestrians and pedestrian walkways. The objectives of this research are to identify the pedestrian needs and requirements in Kuantan CBD area, to investigate the barriers on pedestrian facilities specifically the pedestrian lighting in Kuantan CBD area and to propose pedestrian parameters in improving the pedestrian lighting for pedestrians in Kuantan CBD area. Different methods of research are conducted which include literature review, survey method by means of questionnaire, interview and site observation before proceeding to data analysis and followed by conclusion and recommendation. At the end of this research, the study will able to identify the pedestrian needs and requirements as well as barriers on the implementation of pedestrian lighting in Kuantan CBD area. The improvement on the pedestrians’ connectivity, safety, comfort and security especially at night are obtained through the improvement and implementation of pedestrian lighting with the most suitable placement and design in Kuantan CBD area.